Tinjauan Kriminologis Terhadap Kejahatan Penipuan Dalam Proses Seleksi TNI-AD Dengan Modus Kenalan Panitia Di Wilayah Hukum Pengadilan Negeri Kupang : Studi Kasus dalam Putusan Nomor: 131/Pid.B/2022/PN Kpg - David, David Timothy Ryopitz Ndaong; Rudepel Petrus Leo; Orpa Ganefo Manuain (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the factors that cause fraud in the Indonesian Army (TNI-AD) selection process, using the acquaint committee modus operandi, and to address these issues based on Decision Number 131/Pid.B/2022/PN Kpg from a criminological perspective. This study uses an empirical juridical method with a qualitative approach, through literature review, analysis of court decisions, and interviews with relevant parties. The research results show that the fraud crime is influenced by two main factors: internal and external factors. Internal factors include the perpetrator’s economic condition, which encourages deviant behavior. Meanwhile, external factors include the victim’s needs, the social relationship between the perpetrator and the victim, and the opportunity exploited by the perpetrator. Furthermore, based on analysis using the fraud triangle theory, it was found that the elements of pressure, opportunity, and rationalization collectively drive the perpetrator to commit fraud. Efforts to combat fraud are carried out through two approaches: preventive and repressive. Preventive efforts involve legal education, raising public awareness, and monitoring practices that have the potential to lead to crime. Repressive efforts involve enforcing the law against perpetrators in accordance with applicable regulations to provide a deterrent effect and maintain public order. Based on the research results, it can be concluded that the fraud in this case was not only caused by the perpetrator’s intentions, but also influenced by economic conditions, social relationships, and available opportunities. Therefore, synergy between law enforcement and the community is needed in efforts to prevent and address fraud